Germline BRCA Mutation and Clinical Outcomes in Breast Cancer Patients Focusing on Survival and Failure Patterns: A Long-Term Follow-Up Study of Koreans - Kim, Hakyoung (Medicina (Kaunas), 2020)
Background and Objectives: This study aimed to evaluate the effect of a BRCA mutation on survival and failure patterns, focusing on the risk of ipsilateral recurrence and contralateral breast cancer in patients. Materials and Methods: We retrospectively reviewed medical records of 300 patients with breast cancer who underwent genetic screening for BRCA1/2 genes and were treated at Samsung Medical Center between 1 January 2000 and 31 December 2010. Ultimately, clinical outcomes of 273 patients were analyzed. Results: The median follow-up duration was 102 months (range, 1 to 220 months). Patients with BRCA1/2-mutated tumors had a shorter 10-year disease-free survival (DFS) rate compared to those with non-mutated tumors (62.8% vs. 80.0%, p = 0.02). Regarding failure patterns, patients with BRCA1/2-mutated tumors showed a higher incidence of contralateral breast cancer than those with non-mutated tumors (BRCA1/2 non-mutated vs. mutated tumors: 4.9% vs. 26.0%, p < 0.001). BRCA mutation status remained a significant prognostic factor for contralateral breast recurrence-free survival (HR: 4.155; 95% CI: 1.789–9.652; p = 0.001). Korean patients with a BRCA mutation showed inferior DFS compared to those without a BRCA mutation. Conclusions: BRCA mutation status is a strong predictor of recurrence in contralateral breast cancer. Strategies such as prophylactic treatment and active surveillance should be discussed with breast cancer patients who have a BRCA mutation.